In-Home Secondhand Smoke Exposure Among Urban Children With Asthma: Contrasting Households With and Without Residential Smokers. Issue 2 (March 2019) - Wu, Tianshi David; Eakin, Michelle N.; Rand, Cynthia S.; Brigham, Emily P.; Diette, Gregory B.; Hansel, Nadia N.; McCormack, Meredith C.
Abstract : Context: Secondhand smoke exposure (SHSe) affects up to half of all children in the United States. Many studies have identified factors associated with in-home SHSe, but few have contrasted these factors between households with and without residential smokers. In the latter case, exposure occurs from only external sources that enter the home, such as visitors or environmental incursion. Objective: Among children with SHSe at home, to examine demographic and psychosocial differences between households with and without residential smokers. Design: Baseline analysis of an observational cohort. Setting: Baltimore City, Maryland. Participants: A total of 157 children with asthma, aged 5 to 12 years. Measures: At-home airborne nicotine, caregiver-reported depression, asthma-related quality of life, functional social support, and demographics. Univariable comparisons were performed between SHS-exposed households with and without residential smokers. Multivariable logistic regression models were fit to examine associations between measured factors and absence of residential smokers. Results: Children (78.3%) had at-home SHSe. Of these, 40.7% lived in households without residential smokers. Compared with households with residential smokers, these caregivers endorsed stronger beliefs in SHS harms and also worse functional social support and asthma-related stress, despite no differences in asthma morbidity. In adjusted models, SHS-exposed children with caregivers in the lowest tertile of functional social support (adjusted odds ratio, 3.50; 95% confidence interval, 1.12-10.99), asthma-related quality of life (2.90; 1.06-7.95), and those living alone (5.28; 1.26-22.15) had at least twice higher odds of having exclusively external SHSe than the highest tertile ( P trends < .05). Conclusions: In-home SHS exposure remains alarmingly high in urban environments. However, a substantial proportion of this exposure appears to be occurring only from external sources that enter the home. Caregivers in these homes had higher desire but lower agency to avoid SHSe, driven by lack of functional support and physical isolation. Public policies targeting these factors may help remediate exposure in this especially vulnerable population.